2022
DOI: 10.3168/jdsc.2022-0238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc source (zinc sulfate or zinc hydroxychloride) on relative abundance of fecal Treponema spp. in lactating dairy cows

Abstract: The present study describes the difference in fecal microbiome between cows fed supplemental zinc either in a sulfate or hydroxychloride form. Supplemental zinc hydroxychloride under ad libitum feeding conditions decreased Treponema spp., particularly those sequences within Treponema 2, by 67% compared with a similar diet with zinc sulfate, whereas other changes in the fecal microbiome were minimal. The shift in Treponema spp. from zinc source could reflect a fecal microbiome response to zinc availability, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Preferential intake period consisted of heifers provided simultaneous free-choice access white salt-based trace mineral supplements containing sulfate ( SUL ) or hydroxychloride ( HYD ; Selko IntelliBond ® , Selko Feed Additives) sources of Cu, Mn, and Zn for 28 d (days 28 to 55). The 28-d period of supplementation of SUL and HYD utilized herein was selected based on previous studies demonstrating that 21 d of supplementation of Zn hydroxychloride was sufficient to alter the fecal microbiome ( Wenner et al, 2022 ) and alter the intestinal morphology and initiate a systemic inflammatory response compared to Zn sulfate supplementation ( Horst et al, 2020 ). Both sources of Cu, Mn, and Zn were mixed into their respective white salt-based trace mineral supplement containing all macro and trace minerals, except for Cu, Mn, and Zn, and offered in a loose meal form.…”
Section: Methodsmentioning
confidence: 99%
“…Preferential intake period consisted of heifers provided simultaneous free-choice access white salt-based trace mineral supplements containing sulfate ( SUL ) or hydroxychloride ( HYD ; Selko IntelliBond ® , Selko Feed Additives) sources of Cu, Mn, and Zn for 28 d (days 28 to 55). The 28-d period of supplementation of SUL and HYD utilized herein was selected based on previous studies demonstrating that 21 d of supplementation of Zn hydroxychloride was sufficient to alter the fecal microbiome ( Wenner et al, 2022 ) and alter the intestinal morphology and initiate a systemic inflammatory response compared to Zn sulfate supplementation ( Horst et al, 2020 ). Both sources of Cu, Mn, and Zn were mixed into their respective white salt-based trace mineral supplement containing all macro and trace minerals, except for Cu, Mn, and Zn, and offered in a loose meal form.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the cows fed the IO diet had a lower relative abundance of Alistipes, similar to previous results [58], and was attributed to the reduced fibrous substrate of IS cows feeding. Treponema is a known fiber degrader and was positively correlated with fiber degradation [59], which was also one of the reasons for the lower fiber degradation in the cows fed the IS diet. Similarly, the decrease in Lachnospiraceae_AC2044_group in the cows fed the IO and IS diet may also be associated with the decrease in NH 3 -N reported in our companion study [60], and it has been reported to be negatively correlated with branchedchain volatile fatty acids in yaks grazing on low-CP (10%) and high-NDF shrubs [61].…”
Section: Fecal Bacteria Abundancementioning
confidence: 97%